SISTEM UJI TAK RUSAK BERBASIS ULTRASONIK UNTUK KONTROL KUALITAS PADA FABRIKASI BATA TIMBAL - Rhakamerta Hijazi; Suprijanto; Freddy Haryanto; Ahmad Haerudin; Yusuf Giri Wijayaa; Jos Budi Sulistyo (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2024)
BATAN has the authority to improve the quality of lead brick production, which is still fabricated conventionally. Therefore, a non-destructive testing system has been developed, consisting of a Partial Immersion Technique transducer used to maintain a perpendicular scanning angle due to the uneven surface of the lead brick, an un0rick board used for its flexibility and good capability in generating high-voltage electrical pulses and high sampling frequency, and a laptop. The result is the optimization of ultrasonic parameters, with a transducer frequency of 500 KHz and a pulse length of 0.5 Î¼s. Additionally, tests were conducted on three cases. A standard lead brick used as a reference has a propagation speed of 2.156 m/s. The lead brick with artificial defects had the first defect location estimated at 23.32 mm with an error of 16.62%, the second defect location estimated at 25.1 mm with an error of 0.44%, the third defect location estimated at 36.17 mm with an error of 9.57%, and the fourth defect location estimated at 9.38 mm with an error of 6.2%. The third case, a lead brick with natural defects, had the defect location estimated at 26.77 mm with an error of 1.08%.